2007
DOI: 10.1172/jci29709
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin modulates inflammatory reactions via calreticulin receptor–dependent clearance of early apoptotic bodies

Abstract: Obesity and type 2 diabetes are associated with chronic inflammation. Adiponectin is an adipocyte-derived hormone with antidiabetic and antiinflammatory actions. Here, we demonstrate what we believe to be a previously undocumented activity of adiponectin, facilitating the uptake of early apoptotic cells by macrophages, an essential feature of immune system function. Adiponectin-deficient (APN-KO) mice were impaired in their ability to clear apoptotic thymocytes in response to dexamethasone treatment, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
273
2
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(292 citation statements)
references
References 54 publications
5
273
2
12
Order By: Relevance
“…Adiponectin (ACRP30) is the most abundant adipocytokine, presenting in plasma in globular, trimer, hexamer and highmolecular weight (HMW) isoforms (Fruebis et al 2001;Takemura et al 2007). Unlike leptin, adiponectin secretion is inversely correlated with fat mass and promotes antiinflammatory, antiangiogenic, antiatherogenic and vasodilatory action, exerting also beneficial effects on lipid and glucose profiles (Gustafson 2010).…”
Section: Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin (ACRP30) is the most abundant adipocytokine, presenting in plasma in globular, trimer, hexamer and highmolecular weight (HMW) isoforms (Fruebis et al 2001;Takemura et al 2007). Unlike leptin, adiponectin secretion is inversely correlated with fat mass and promotes antiinflammatory, antiangiogenic, antiatherogenic and vasodilatory action, exerting also beneficial effects on lipid and glucose profiles (Gustafson 2010).…”
Section: Adiponectinmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α) levels strongly correlate with BMI (Takemura et al 2007) and have been implicated in the demential process, though inconsistently (Une et al 2011). Guerreiro et al (2007) showed that in MCI and AD patients there was a significant raise in the percentage of monocytes producing pro-inflammatory interleukins (IL-1β, IL-6, IL-12) and TNF-α when compared with healthy controls.…”
Section: Visfatin and Rbp-4mentioning
confidence: 99%
“…However, as Tcadherin lacks an intracellular domain, the specific biologic function of any Ad/T-cadherin interaction remains unknown. Calreticulin (CRT), a multifunctional chaperone protein binding calcium ions, in concert with its adaptor protein CD91, has been identified by Walsh's group (40,60) to be yet another receptor for Ad. Ad's interaction with CRT/CD91 has been shown to exert endothelial anti-inflammatory and vasculoprotective effects.…”
Section: Fig 1 Structure Of Ad (Human)mentioning
confidence: 99%
“…25 Adiponectin, an abundant circulating adipocyte-derived cytokine that is decreased in obese individuals, can opsonize apoptotic cells and promote engulfment through interaction with calreticulin and CD91 on the phagocyte surface. 26 Interestingly, calreticulin even mediates uptake of viable cells if the interactions between CD47 on the viable target cell and signal regulator protein-a (SIRPa,) on the phagocyte are disrupted. 13 The former is an integrin-associated protein, and the latter is a heavily glycosylated transmembrane protein with an immunoreceptor tyrosine-based inhibition motif domain.…”
Section: Positive Regulators Of Uptake Dying Cellmentioning
confidence: 99%